Does Labor Market Hysteresis Hold in Low Income Countries? - Olanipekun, Ifedolapo Olabisi; Akadiri, Seyi Saint; Olawumi, Osundia; Bekun, Festus Victor (International Journal of Economics and Financial Issues, 2017)
This study tests for labor market hysteresis in low income countries while accounting for structural break in the unemployment rates. This is to verify if unemployment in low income countries will return back to natural rate of unemployment in the long run using data from Nigeria and South Africa. It follows the procedure for single structural break unit root test by Zivot and Andrews (1992). The empirical result indicates that accounting for structural break makes the unemployment rate series stationary for Nigeria; hence, shocks to the unemployment rates will have temporary effects. Contrarily, evidence of hysteresis was found in South Africa's unemployment rates series because it was not stationary. Nigeria's macroeconomic policy can aim at lowering inflation through a contractionary policy, it will temporarily increase unemployment but it will return back to its natural state, but structural reforms that will prompt shock on South African unemployment will increase the persistence of hysteresis. Keywords: Unemployment, Hysteresis, Unit root, Stationarity. EL Classifications: C22; E24; J16; J21